Inventory Control of Cotton Combed 30s Raw Materials to Minimize the Total Inventory Cost of MSMEs Kamal Konveksi Central Lombok - Randitya Maulana; Sumiati Sumiati (PT Mattawang Mediatama Solution, 2023)
This study aims to control the cotton combed 30s raw materials inventory in Kamal Convection MSMEs in Central Lombok using the EOQ (Economic Order Quantity) and POQ (Period Order Quantity) methods to minimize the total inventory cost. The EOQ and POQ methods are proposed as suggestions for the most optimal improvement of inventory control. The calculations using the company's method show that the purchased quantity of cotton combed 30s raw material supplies an average of 1.843 kg with a purchase frequency of 12 times a year, and a total inventory cost of Rp. 19.363.400. The proposed EOQ method reveals the quantity of inventory purchased is 3.463 kg with a purchase frequency of 6 times in one year, and the total inventory cost is Rp. 13.157.959. Meanwhile, the proposed POQ method indicates the quantity of inventory purchased is 11.059 kg with a purchase frequency of 2 times in one year, and the total inventory cost is Rp. 23.072.100. Based on the calculation results, the use of the EOQ method is the most optimal purchase of cotton combed 30s raw materials to reduce inventory costs. The difference in total inventory cost between the EOQ method and the proposed POQ method is Rp. 9.914.141. The total inventory cost difference between the EOQ and company methods is Rp. 6.205.441. Based on this analysis, controlling the inventory of raw material for cotton combed 30s at Kamal Convection is relatively ineffective. Based on the results of the calculation analysis using the EOQ method, it is the most optimal method for reducing the cost of supplying raw material for cotton combed 30s at Kamal Konveksi.